Digital Marketing Training and Visual Identity Design as a Strategy for Economic Recovery of the People of Kucur Village in Malang Regency from the Impact of the COVID-19 Pandemic - Sultan Arif Rahmadianto; Aditya Nirwana; Ayyub Anshari Sukmaraga (Journal of Community Practice and Social Welfare, 2022)
The Medium-Term Development Plan (RPJM) of Kucur Village from 2019 to 2025 focuses on the community's economic recovery due to the COVID-19 pandemic. This Community Service activity is a form of support for the planning document for 6 (six) years. In addition, it is an elaboration of the vision and mission of the Village (RPJM). The problem faced by the people of Kucur village that has been identified is that Kucur village has significant tourism potential but has not been fully managed optimally. On the other hand, the Kucur village tourism activist team does not fully understand digital marketing, which is now a trend and an effective way during the COVID-19 pandemic. In addition, practical solutions are needed to restore the community's economy immediately. Departing from these problems, an increase in the competence of the Kucur village tourism activist team, especially the Gunung Sari Valley, in the field of marketing; in the form of copywriting training and its implementation on social media; 2) optimization of smartphones and applications for digital marketing activities such as simple design applications and video editing, and 3) Design of the visual identity of the Gunung Sari Valley (LGS) and its implementation to various media. As a result of this activity, there is an increase in public understanding to optimize LG S Nature Tourism through digital marketing. Furthermore, the visual identity developed by the Community Services team received a positive response from the LGS management team. It aroused the manager's interest in producing merchandise and developing other facilities for monetization.